1992
DOI: 10.1097/00000658-199203000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Donor Hyperglycemia as a Minor Risk Factor and Immunologie Variables as Major Risk Factors for Pancreas Allograft Loss in a Multivariate Analysis of a Single Institutionʼs Experience

Abstract: The impact of multiple donor and recipient variables on functional survival of 307 cadaveric pancreas allografts transplanted in 253 recipients at the authors' institution between July 25, 1978 and September 4, 1990 was determined using the Cox proportional hazards regression model. Relative risk of graft loss was calculated for all cases as well as for technically successful (TS) ones. Factors with an impact in descending order of significance for TS cases were immunosuppression (RR = 3.9 for double-drug vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…But for pancreas recipients, the effect is not as clearly defined. Early studies showed an increased rate of graft loss with a higher number of HLA MMs, at least at the HLA-A, -B, or -DR loci (16,17). Yet, more contemporary analyses do not support those early findings.…”
Section: Discussionmentioning
confidence: 95%
“…But for pancreas recipients, the effect is not as clearly defined. Early studies showed an increased rate of graft loss with a higher number of HLA MMs, at least at the HLA-A, -B, or -DR loci (16,17). Yet, more contemporary analyses do not support those early findings.…”
Section: Discussionmentioning
confidence: 95%
“…254 Although pancreas grafts from both pediatric 262 and older donors 263 have been successfully transplanted, 107 we 107 and others 264,265 are selective. Whatever the age range, one group has shown that the outcomes for paired grafts from the same donor are similar in KTA and SPK recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Absolute contraindications for pancreas donation are active infection or malignancy, positive serologic evaluation for hepatitis B surface antigen (HBsAg), hepatitis C virus (HCV), human immunodeficiency virus (HIV), and human T cell lymphotropic virus type 1 (HTLV-1), proved diabetes mellitus, pancreatitis (acute/chronic), severe pancreatic steatosis or edema, previous pancreatic surgery and intra-abdominal sepsis. Donor hyperglycemia is common because of stress condition and use of high dose corticosteroids and not a contraindication for use of the pancreas, although it may contribute as a minor risk factor for long-term graft loss (Gores, et al, 1992). Most surgeons only select younger non-obese donors (age 10-50 years, weight 30-100 kg) who are hemodynamically stable without need to high doses of vasopressors.…”
Section: Surgical Aspects Of Pancreas Graft Procurement From the Decementioning
confidence: 99%